2023
DOI: 10.3344/kjp.23039
|View full text |Cite
|
Sign up to set email alerts
|

Perampanel ameliorates nitroglycerin-induced migraine through inhibition of the cAMP/PKA/CREB signaling pathway in the trigeminal ganglion in rats

Abstract: Background Perampanel, a highly selective glutamate AMPA receptor antagonist, is widely used to treat epilepsy. Since the existence of common pathophysiological features between epilepsy and migraine, the aim of this study was to investigate whether perampanel could exert an antimigraine effect. Methods Nitroglycerin (NTG) was used to induce a migraine model in rats, and the model animals were pretreatment with 50 μg/kg and 100 μg/kg perampanel. The expression of pituit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…These studies suggest that targeting these pathways could offer therapeutic benefits for migraine patients. Various pharmacological agents are explored across the studies, including natural compounds ( 58 , 65 ), traditional Chinese medicines ( 59 , 66 ), and novel drugs ( 62 , 67 ). These interventions aim to modulate molecular targets associated with migraine pathogenesis, highlighting the potential of diverse treatment modalities.…”
Section: Resultsmentioning
confidence: 99%
“…These studies suggest that targeting these pathways could offer therapeutic benefits for migraine patients. Various pharmacological agents are explored across the studies, including natural compounds ( 58 , 65 ), traditional Chinese medicines ( 59 , 66 ), and novel drugs ( 62 , 67 ). These interventions aim to modulate molecular targets associated with migraine pathogenesis, highlighting the potential of diverse treatment modalities.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the signi cant results, publications that studied the effect of PER on the phosphorylation of GluA1 receptors are scarce and inconclusive. A recent study by Zhai et al (2023), evaluated the effect of the drug on the expression of PKC (protein that phosphorylates GluA1) and phosphorylation of GluA1, trying to explain the effect of PER on migraine, through the expression of PKC and other enzymes, without nding a clear correlation [49]. Kim et al (2019), found that PER in uences the phosphorylation of GluA1 depending on the exposure time, in the same way that it alters the expression of several enzymes that phosphorylate the GluA1 subunit, such as PKC and CAMKII [50].…”
Section: Discussionmentioning
confidence: 96%